State Challenges to Plyler v. Doe: Undocumented Immigrant Students and Public School Access (Perspectives on Legal Issues in Education) - Lenford C. Sutton; Tricia J. Stewart (Educational Considerations, 2013)
This article presents a review and an analysis of selected state laws and initiatives that have attempted to restrict public school access for undocumented immigrant children in the wake of the landmark U.S. Supreme Court decision of Plyler v. Doe.
Keywords: challenges; Plyler v. Doe; California; U.S. Constitution; public schools; state-funded; undocumented; students; federal immigration laws; proposition